PRE-SERVICE TEACHERS' PERCEPTIONS ON ASSESSMENT - Ida Isnawati; Nursamsu Nursamsu (UPT Bahasa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Pre-service teachers as the future educators must be thoroughly prepared to become professional teachers. Having assessment is one crucial skill to be professional teachers. This study aims to explore the perceptions of pre-service teachers towards assessment. Sixty pre-service teachers from UIN Sayyid Ali Rahmatullah Tulungagung participated in this research. They completed a questionnaire designed to evaluate their knowledge and beliefs about assessment. The findings suggest that while the majority have a positive view of assessment, a small number hold negative perceptions indicating their lack understanding of assessment. Therefore, it is necessary to improve their understanding of assessment to ensure they are adequately prepared to become professional teachers.